ELECTRONIC MANAGEMENT AND ITS RELATIONSHIP TO THE QUALITY OF EDUCATIONAL SERVICES (Study on the Faculty of Economics University of Benghazi) - المنصوري فاطمة (Scientific Journal of University of Benghazi, 2022)
The study used the descriptive analytical approach and aimed to identify the relationship of electronic management with its four dimensions (Electronic Planning, Electronic Regulation, Electronic Guidance, Electronic Control) on the educational services quality, as well as to determine the correlation of statistical significance between electronic management and the educational services quality in the Faculty of Economics, University of Benghazi. To achieve this study, a questionnaire was designed and distributed to a sample of the study population consists of (340) Faculty of Economics, University of Benghazi teaching members, which is located in Benghazi. (85) questionnaires were distributed, and (68) questionnaires valid for statistical analysis were retrieved. This study reached several results, the most important of which is that the strong impact of electronic management on the educational services quality, as well as the existence of a strong correlation with statistical significance between electronic management and educational services quality in the Faculty of Economics. The most important recommendation of this study is keeping the college abreast of modern environmental changes, hiring experts to develop electronic plans and control all its operations and improve teaching staff capacities through training programs and securing all resources in information processing.